Establishing the analytical relationships for mass and volumetric mass fractions for hybrid boyant aircraft - UlHaque, Anwar; Asrar, Waqar; Omar, Ashraf Ali; Sulaeman, Erwin; Syed Mohamed Ali, Jaffar (2015)
The current data bank of operational empty mass fraction of airships is based on available data obtained from existing and historical airships. For any design related activity, regression analysis on existing data bank of airships will not be able to provide the true picture of mass fractions of hybrid airships. This situation becomes more critical when a wing is attached to the hull of airship and there is no proven algebraic formulation that is able to distinguish between electric and fuel powered propulsion. In the present work, by using theoretical approach; new analytical relationships for mass and volume fraction are derived to estimate the mass and volume fractions of fuel-powered-hybrid buoyant aircraft. Existing formulas for the determination of volumetric weight fractions of fuel powered airship are also discussed. Established relationship of mass and volume fractions will be useful to estimate the masses and dimensions of individual sub-assemblies of hybrid buoyant aircraft.